9 Transforming transition for paediatric ibd patients in northern ireland. (5th April 2017) - Little, R; McLoughlin, L; Szabo, A
Abstract : Background: The Paediatric Gastroenterology team in Belfast has been continuously developing their service to facilitate efficient transfer of adolescent care to Adult Gastroenterology. Initially this process was by referral letter only however, in view of the increasing prevalence of Inflammatory Bowel Disease (IBD), establishing a well-structured transition clinic was essential. We sought to elucidate the level of preparedness for, and experience at, transition clinic from our adolescent attendees. Method: We devised a questionnaire which was distributed to all adolescent patients attending transition clinic over a six month period, which they completed anonymously. Data was then collated. Results: Of the twenty two patients surveyed 100% rated the quality of care at transition clinic as excellent or good. 100% agreed they were well supported by the medical and nursing staff present, 82% of which agreed the clinic adequately prepared them for moving to Adult Gastroenterology care. However, only 50% of patients knew their medication names and doses. 32% wanted more advice regarding symptom management and investigations. 75% of patients had ongoing dietetic and psychology input. Concern regarding continuity of these valuable services and the loss of a supportive relationship with the paediatric nurse specialist were the main perceived stressors and anxieties for our patient cohort. Conclusions: Over the last eight years the Paediatric Gastroenterology team has successfully established transition clinics with all five trusts across the province. Collaboration between the Paediatric and Adult Gastroenterology teams in Northern Ireland has transformed the continuity, safety and patient experience for young people with IBD transitioning between our expert services.